Interaction of Mycobacterium tuberculosis Cell Wall Components with the Human Natural Killer Cell Receptors NKp44 and Toll‐Like Receptor 2. (22nd May 2013) - Esin, S.; Counoupas, C.; Aulicino, A.; Brancatisano, F. L.; Maisetta, G.; Bottai, D.; Di, M.; Florio, W.; Campa, M.; Batoni, G.
Abstract We have previously demonstrated that a soluble form of the human NK cell natural cytotoxicity receptor NKp44, binds to the surface of Mycobacterium tuberculosis (MTB). Herein, we investigated the interaction of MTB cell wall components (CWC) with NKp44 or with Toll‐like receptor 2 (TLR2) and the role of NKp44 and TLR2 in the direct activation of NK cells upon stimulation with MTB CWC. By using several purified bacterial CWC in an ELISA, we demonstrated that NKp44 was able to bind to the MTB cell wall core mycolyl‐arabinogalactan‐peptidoglycan (mAGP) as well as to mycolic acids (MA) and arabinogalactan (AG), while soluble TLR2 bound to MTB peptidoglycan (PG), but not to MA or AG. The mAGP complex induced NK cell expression of CD25, CD69, NKp44 and IFN‐γ production at levels comparable to M. bovis Bacillus Calmette–Guérin‐stimulated (BCG) cells. While AG and MA used alone failed to induce NK cell activation, mycobacterial PG‐exhibited NK cell stimulatory capacity. Activation of resting NK cells by mAGP and IFN‐γ production were inhibited by anti‐TLR2 MAb, but not by anti‐NKp44 MAb. Differently, anti‐NKp44 MAb partially inhibited CD69 expression on NK cells pre‐activated with IL‐2 and then stimulated with mAGP or whole BCG. Overall, these results provide evidence that components abundant in mycobacterial cell wall are able to interact with NKp44 (AG, MA) and TLR‐2 (PG), respectively. While interaction of TLR2 with mycobacterial cell wall promotes activation of resting NK cells and IFN‐γ production, NKp44 interaction with its putative ligands could play a secondary role in maintaining cell activation.